Optical characterization of tin oxide nanomaterial - Sowl, S. (Animo Repository, 2008)
SnO2 nanomaterial was synthesized using the horizontal high vacuum thermal deposition technique. The products from a growth temperature of 1200oC provided photoluminescence and fluorescence. SEM images revealed belt and stick like nanostructures with size as small as 40 nm and widths at the micrometer range. EDX analysis revealed the atomic composition 2:1 of oxygen and tin. Samples grown for three hours have a photoluminescence signal at 454 nm while samples with a growth time of two hours were at 438 nm. The peaks correspond to blue visible light emission, which is a manifestation of structural defects during synthesis.